(untitled) (Journal Of Educational and Psychological Researches, 2016)
The study aims detection teaching modalities adopted relationship in Jerash University exactly the classroom, and to achieve the goal of the study was to develop a questionnaire consisting of (39) items, and was achieving validity and reliability have, then sent to a sample of professors made up the university from (122) university professor of the total (172) professor, and they study population. Study found a relationship between the teaching methods of the four their strategies with classroom management, and as a result the overall average level, while Hspt critical thinking at the highest correlation with classroom discipline management relationship strategy, while the relationship between the workshops and concerns and activities strategy’ve got less correlation exactly classroom. The research presents a number of appropriate recommendations.